Fundamentals of financial accounting - Welsch, Glenn A.; Anthony, Robert N. (Homewood, Ill. : R. D. Irwin, 1977)
This book is an introduction to financial accounting , which has as its primary subject the communication of relevant financial information to external parties. The key to sound use of financial statements is to understand what they do and do not say, the measurement approach used, and the standards observed in their development.
Includes index.
jbi, 09/03/2018
Loans
Keywords: Accounting